Anti-Candida activity of Quercus infectoria gall extracts against Candida species - Nur Saeida Baharuddin; Hasmah Abdullah; Wan Nor Amilah Wan Abdul Wahab (Wolters Kluwer Medknow Publications, 2015)
Background: Galls of Quercus infectoria have been traditionally used to treat common ailments, including yeast infections caused by Candida species. Objective: This study aimed to evaluate the in vitro anti-Candida activity of Q. infectoria gall extracts against selected Candida species. Materials and Methods: Methanol and aqueous extracts of Q. infectoria galls were tested for anti-Candida activity against Candida albicans, Candida krusei, Candida glabrata, Candida parapsilosis and Candida tropicalis. The minimum inhibitory concentrations were determined using the two-fold serial dilution technique of concentrations ranging from 16 mg/ml to 0.03 mg/ml. After 24 h, the minimum fungicidal concentrations were determined by subculturing the wells, which showed no turbidity on the agar plate. Potential phytochemical group in the crude extracts was screened by phytochemical qualitative tests and subsequently subjected to the gas chromatography-mass spectrometry analysis. Results: Both methanol and aqueous extracts displayed substantial anti-Candida activity and pyrogallol was the major component of both crude extracts. Conclusions: Data from current study suggested that Q. infectoria gall extracts are a potential source to be developed as anti-candidiasis.